THE RESEARCH REVIEW ABOUT USING YOUTUBE ENGLISH CHANNEL IN IMPROVING STUDENTS’ ENGLISH FOREIGN LANGUAGE SKILLS - Mahmudah, Khotimah (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2022)
The YouTube app is a platform that allows users to upload creative and informative videos and then show them to other users. YouTube users are spread worldwide, including Many native English speakers and English language experts who are also involved in creating English language channels through YouTube that allow viewers to learn English from authentic sources. However, there are not many research studies that discuss the use of YouTube videos to improve English learning. The primary purpose of this research is to explore a preliminary study of the use of YouTube channels related to learning English. The research focuses on improving students' English skills. The technique of collecting data is that the researcher focuses on articles retrieved through internet search engines in the last four years, starting in 2019 and ending in 2022. The articles were selected manually and reviewed systematically—search keywords related to YouTube English Channel. Then, the findings were reviewed and categorized into two problems: the effectiveness of using English YouTube Channels based on the participant's point of view and implementing YouTube Videos as Learning Resources in English classes to improve specific language-Skills. The results show several articles reveal positive indications of using English learning resources through the English YouTube Channel. English Language Education Practitioners can find this valuable knowledge in conducting practical learning and developing various instructional tasks based on the YouTube English Channel Platform in developing EFL students' skills.